Analysis of scientific production related to sports psychology in sports science journals of Portuguese language - Coimbra D.R.* (2018)
© 2018, Universidade Estadual de Maringa.The aim of this study was to analyze scientific production related to sport psychology (SP) in journals of sports science. The electronic search in 15 journals of physical education was performed in August 2016. Altogether, 145 articles were selected. The first publication occurred in 1997. It was observed an increase in publications from 2007. The journal that most published about SP was Journal of Physical Education of State University of Maringá with 24 publications. The institutions UEM, UFJF, UFMG, USP and UDESC showed at least 10 publications each. Paraná, São Paulo and Minas Gerais were states with most publications. It was observed that most studies had cross-sectional design. At total, 49 sports were investigated, volleyball was the most studied, followed by Soccer and Basketball. Motivation was the theme of most of studies, especially in Soccer, as well as stress, anxiety and mood states. We concluded that there was an increase in scientific production about SP in the last decade. Themes applied to sport as mental training, techniques of activation and relaxation requires investigation.